Pengetahuan ibu tentang stunting di wilayah kerja Puskesmas Bukit Sari Kabupaten Kepahiang - Prajna Galuh Pangestuti; Tri Sunarsih; Lily Yulaikhah (Holistik Jurnal Kesehatan, 2024)
Background: Stunting is a chronic nutritional problem experienced by Indonesia. Stunting is a condition of growth failure in children caused by chronic malnutrition so that children are too short for their age. It is important to conduct research on stunting in order to assist the government in implementing work programs to reduce the incidence of stunting. Purpose: To determine mothers' knowledge about stunting. Method: Quantitative research with descriptive design. The study was conducted in the Bukit Sari Health Center Working Area, Kepahiang Regency in 2023. The population in this study were all mothers who had toddlers. The sample size can be calculated using the Slovin formula and 87 respondents were obtained. The instrument was a questionnaire to assess the description of mothers' knowledge about stunting and data analysis using univariate. Results: the level of mothers' knowledge about stunting was 49.42% good knowledge, 41.38% sufficient knowledge and 9.20% less knowledge. Conclusion: The description of the level of mothers' knowledge about stunting shows that most of the mothers' knowledge is in the good category, namely 49.43%. Suggestion: The health center is advised to conduct intensive monthly outreach to mothers who have toddlers regarding stunting, prevention and supervision to avoid stunting in children and the risks that follow..   Keywords: Knowledge; Mother; Stunting.   Pendahuluan: Stunting merupakan masalah gizi kronis yang dialami oleh Negara Indonesia. Stunting merupakan kondisi gagal tumbuh pada anak yang diakibatkan kekurangan gizi kronis sehingga anak terlalu pendek untuk seusianya. Pentingnya dilakukan penelitian tentang stunting ini agar dapat membantu pemerintah dalam menjalankan program kerja untuk menurunkan angka kejadian stunting. Tujuan: Untuk mengetahui pengetahuan ibu tentang stunting Metode: Penelitian kuantitatif dengan desain deskriptif, dilakukan di wilayah kerja Puskesmas Bukit Sari Kabupaten Kepahiang pada tahun 2023. Populasi dalam penelitian ini adalah semua ibu yang mempunyai anak balita. Besar sampel dapat dihitung dengan menggunakan rumus slovin dan didapatkan sebanyak 87 responden. Instrumen penelitian berupa kuesioner untuk menilai gambaran pengetahuan ibu tentang stunting dan analisis data menggunakan univariat. Hasil: Tingkat pengetahuan ibu tentang stunting 49.42% berpengetahuan baik, 41.38% berpengetahuan cukup dan 9.20% berpengetahuan kurang. Simpulan: Gambaran tingkat pengetahuan ibu tentang stunting menunjukan bahwa sebagian besar pengetahuan ibu dalam kategori baik yaitu 49.43%. Saran: Pihak puskesmas agar melakukan penyuluhan berupa sosialisasi bulanan yang intensif kepada ibu-ibu yang mempunyai anak balita mengenai stunting, pencegahan dan pengawasannya untuk menghindari terjadinya stunting pada anak dan risiko yang mengikutinya.   Kata Kunci: Pengetahuan; Ibu; Stunting.